LUMUT SEJATI DI KAWASAN CAGAR ALAM GUNUNG PAPANDAYAN GARUT, JAWA BARAT - Windadri, Florentina Indah (BERITA BIOLOGI, 2014)
Research on moss diversity in the Papandayan Nature Reserve has been conducted covering the western and eastern areas of the Nature Reserve. Fifty one species of mosses from 14 families and 30 genera were recorded and collected with Dicranaceae as the dominant family.Four species of mosses (Papillaria crocea (Hampe) Jaeg., Barbella rufifolioides (Broth.) Broth., Ctenidium luzonense Broth. and Trichostomum brachydontium Bruch ex Mull.Hal are reported here as new records to Java.